An analysis of cervical cancer by implementing fuzzy logic matrix algorithm using python programming - Radhika, K.; Anbalagan, S.; Alexander, C. (AIP conference proceedings, 2021)
Cervical cancer develops in the cells lining of cervix which is the lower part of the uterus (womb). Cancer develops when cells in the cervix grow out of control due to changes in the DNA. This research herewith interviewed and collected the data from 193 cervical cancer patients in “Thanjavur cancer care and Research Centre” and analyzed by using Fuzzy Logic Matrix (CEDT matrix) algorithm applying with python program and which risk factor play an important role among other factors causing cervical cancer is found out.